A mechanistic updated overview on lycopene as potential anticancer agent - Ozkan, Gulay; Gunal-Koroglu, Deniz; Karadag, Ayse; Capanoglu, Esra; Cardoso, Susana M.; Al-Omari, Basem; Calina, Daniela; Sharifi-Rad, Javad; Cho, William C. (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2023)
The potent relation between lycopene intake and reduced incidence of a variety of cancers has an increasing interest. This comprehensive review aims to highlight the in vivo and in vitro research evaluating the anticancer mechanisms of lycopene by underlining the experiment conditions. In addition to these, the general characterization of lycopene has been explained.A collection of relevant scientific pharmacological articles from the following databases PubMed/MedLine, Web of Science, Scopus, TRIP database, and Google Scholar on the mechanisms of anticancer molecular action and cellular effects of lycopene in various types of tumors was performed. The anticancer potential of lycopene has been described by various in vitro cells, animal studies, and some clinical trials. It has been revealed that the anticancer potential of lycopene is mainly due to its powerful singlet-oxygen quencher characteristics, simulation of detoxifying/antioxidant enzymes production, initiation of apoptosis, inhibition of cell proliferation and cell cycle progression as well as modulations of gap junctional communication, the growth factors, and signal transduction pathways. It has been highlighted that the anticancer properties of lycopene are primarily linked to factors including; dose, presence of drug delivery systems, type of cancer, tumor size, and treatment time.
Keywords: Lycopene; Anticancer mechanisms; Apoptosis; Proliferation; Metastasis; Clinical studies; CELL-CYCLE PROGRESSION; IGF BINDING PROTEIN-3; GROWTH-FACTOR-I; PROSTATE-CANCER; GENE-EXPRESSION; DIETARY TOMATO; LUNG-CANCER; Z-ISOMERS; BREAST; Research & Experimental Medicine; Pharmacology & Pharmacy